Changes in plant-soil C-N-P stoichiometry during the vegetation recovery of bare patches caused by plateau pika (Ochotona curzoniae) on the Qinghai-Tibet plateau - Yuan Yuan Duan; Xiao Dan Sun; Huan Yang; Jie Li; Tong Wu; Ni Wang; Zheng Gang Guo; Xiao Pan Pang (Ecological Indicators)
Bioturbation caused by herbivorous fossorial mammals creates extensive bare patches through their burrowing activities. Understanding changes in plant-soil carbon (C), nitrogen (N), and phosphorus (P) stoichiometry during the vegetation recovery of these bare patches is crucial for elucidating the restoration mechanisms of disturbed grassland ecosystems. This study considered plateau pika (Ochotona curzoniae) as the focal species and categorized the bare patches into short-term and long-term bare patches using a spatial substitution strategy, with surrounding vegetated surfaces in disturbed alpine meadows as controls. Results showed that P concentration in plant roots was 32.58% higher in long-term bare patches compared to short-term bare patches. However, no significant changes were observed in C and N concentrations in either plant shoots or roots during vegetation recovery process. Soil N concentrations were 38.78% lower in short-term bare patches and 36.65% lower in long-term bare patches compared to vegetated surfaces. The C:N ratio in plant shoots was 18.26% lower in short-term bare patches than in vegetated surfaces, whereas the soil C:N ratio was 39.42% higher in long-term bare patches compared to vegetated surfaces. However, no changes were observed in the C:P and N:P ratio of both plant and soil during vegetation recovery process of bare patches. These findings indicate that P concentration in plant roots can serve as a reliable indicator of the vegetation recovery process of bare patches caused by plateau pikas. Furthermore, plants in short-term bare patches prioritize rapid growth through resource allocation, while in long-term bare patches, they enhance nutrient use efficiency to achieve greater stability and resilience. These insights into plant-soil nutrient dynamics provide a deeper understanding of ecosystem resilience and recovery processes in disturbed alpine meadows, offering a valuable foundation for more targeted grassland management strategies.